Effect STUDI FENOMENOLOGI RESPON PERTAMA KALI PASIEN DI INTERVENSI PCI (PERCUTANEOUS CORONARY INTERVENTION) DI POLI JANTUNG RSUD ULIN BANJARMASIN TAHUN 2017 (Phenomenological Study Of The First Response Of Patients In Pci Intervention (Percutaneous Coronary Inte - abd basid; candra kusuma negara (CNJ: Caring Nursing Journal, 2018)
ABSTRACT Coronary heart disease is a disease in which the blood vessels that supply food and oxygen to the heart muscle are blocked. Blockage is most often due to the buildup of cholesterol in the walls of coronary arteries. One way to overcome it is by widening the blood vessels, immediately giving drugs. Blockage of blood vessels can also be resolved by the installation of a metal ring called a stent or PCI (Percutaneous Coronary Intervention). The data from WHO in 2014 says that the mortality rate in non-communicable diseases in the world will increase from year to year. In 2012, there were 38 million deaths attributable to various diseases in the non-communicable diseases group of a total of 52 million deaths. In general, this study aims to explore the various experiences of coronary heart patients while undergoing percutaneous coronary intervention (PCI) on the first response they experienced. This study used phenomenology study. Data collection using Indepth Interview on three participants in the poly of Heart of RSUD Ulin Banjarmasin equipped with interview and Informed Consent guidelines. Structured analysis method from Creswell to 6 steps. There is one main theme found in this research that is patient experience in undergoing PCI intervention (Percutaneous Coronary Intervention) on coronary heart patient at RSUD Ulin Banjarmasin. which consists of three sub themes: (1) pre -intervention (2) intervention (3) post-intervention. First response, PC I intervention (percutaneous coronary intervention), coronary heart disease